To solve the expression \(-3^0 + 4.5\), we first need to understand the rules of exponents.
According to the rule, any non-zero number raised to the power of 0 is equal to 1. Therefore:
\(-3^0 = 1\)
Now we can substitute this back into the expression:
\(-3^0 + 4.5 = 1 + 4.5 = 5.5\)
Now let us examine the options provided:
A) \(-3^0 + 4.5 = (-3)^0 + 4.5\) - This is incorrect because \(-3^0 = 1\), not \((-3)^0\).
B) \(-3^0 + 4.5 = -1 \times 3^0 + 4.5\) - This is also incorrect as \(-3^0\) equals 1, not \(-1 \times 3^0\).
C) \(-3^0 + 4.5 = -3 + 4.5\) - This is incorrect since \(-3^0\) equals 1, not -3.
D) \(0 - 3.0 + 4.5 = -3.0 + 4.5\) - This also does not accurately simplify the original expression.
None of the options correctly show the process of solving \(-3^0 + 4.5\) as stated. The correct approach starts with recognizing that \(-3^0 = 1\) and leads to \(1 + 4.5 = 5.5\).
So, to directly answer your question, none of the provided options A, B, C, or D shows the correct process for solving \(-3^0 + 4.5\).